Relationships between knowledge, practice and attitude toward clinical forensic medicine among nurses at the accident and emergency department in hospitals under Bangkok Metropolis - Norkum, Juraiporn; Sriwai, Wimolpak (Thai Journal of Nursing, 2022)
This descriptive study aimed to study relationships between knowledge, practice, and attitude toward clinical forensic medicine among nurses at the accident and emergency department in hospitals under Bangkok Metropolis. A sample of 73 nurses was selected by a simple random sampling method. Data were collected via a test and questionnaire during January to February 2020. The results revealed as follows. 1) Nurses had knowledge at the low level, and their practice in clinical forensic medicine were at the moderate level. 2) There was positive relationship at the low level between knowledge and their practice in clinical forensic medicine (r = 0.308) at p < .01. 3) There was no significant difference of knowledge and practice in clinical forensic medicine between nurses in hospitals providing secondary and tertiary care levels (p > .05)